2013
DOI: 10.4239/wjd.v4.i5.202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethnicity on weight loss among adolescents 1 year after bariatric surgery

Abstract: AIM:To investigate whether or not bariatric surgery weight outcomes vary by ethnicity in a large, nationally representative sample of adolescents. METHODS:The Bariatric Outcomes Longitudinal Database was used for analysis and contains data on surgeries performed on adolescents from 2004 to 2010 from 423 surgeons at 360 facilities across the United States Adolescents (n = 827) between 11 and 19 years old who underwent either gastric bypass or adjustable gastric banding surgery were included in the analysis. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…These observations contrast with publications in which depression and other Axis I disorders were associated with high pre-operative BMI, and with less weight reduction following bariatric surgery. 21,22 From the results of the present study, one might speculate that the higher rates of comorbidity persistence in Caucasians may have exacerbated depression and other psychological impairments for those patients. Although the causes of these racial variations are not clear from the data, increased post-LRYGB Caucasian depression is a significant new observation.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These observations contrast with publications in which depression and other Axis I disorders were associated with high pre-operative BMI, and with less weight reduction following bariatric surgery. 21,22 From the results of the present study, one might speculate that the higher rates of comorbidity persistence in Caucasians may have exacerbated depression and other psychological impairments for those patients. Although the causes of these racial variations are not clear from the data, increased post-LRYGB Caucasian depression is a significant new observation.…”
Section: Discussionmentioning
confidence: 73%
“…This is an important finding, as prior studies have not identified such statistically and clinically significant variations by race in the resolution of hypertension after LRYGB. 13,17,18,22 Consistent with the known increased prevalence of hypertension in the general African-American population, Adams observed the highest rates of hypertension in Asians and African-Americans among morbidly obese patients pre-operative for LRYGB. 1 The results here indicate that the increased African-American propensity for hypertension extends to impaired high blood pressure resolution following LRYGB.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The study, however, enrolled 74.4 percent European Americans, and only 25.6 percent African Americans, and it also studied adult, rather than adolescent, subjects. Based on the evidence, it appears that SES may be a bigger predictor of outcomes than ethnicity; however, not enough data exist to make a definitive conclusion ( 55 , 56 ). What can be assessed is that those of lower SES or living in rural areas further from reputable medical centers, have more post-operative complications and lower success rates than those with better access to resources ( 11 ).…”
Section: Discussionmentioning
confidence: 99%